Rel8: demonstrating the feasibility of delivering an 8-week social skills program in a public mental health setting. (June 2016) - Wauchope, Bronwyn; Terlich, Alissa; Lee, Stuart
Objective: As community mental health services integrate recovery-oriented practices, treatments that focus on skills development and social integration are desirable. This study aimed to examine the feasibility of implementing "Rel8", an 8-week social skills training group adapted to suit a public community mental health setting. Method: A retrospective audit was conducted of quantitative and qualitative data from four groups run between 2011 and 2013. Pre- and post-group measures were collected, assessing self-rated friendships and confidence with social skills and clinician-rated social skill performance. Qualitative feedback about group participation was also collected through use of a developed questionnaire. Results: Analysis revealed significant improvements in participants' confidence with their social skills following group participation, with a trend also found for improved social skill performance. Conclusions: "Rel8", an adapted 8-week social skills training group, is a feasible program in the context of community mental health services. The program added to the recovery-centred practice of the community mental health service while also adding to the diversity of clinician skills for psychosocial-oriented practice.